2020
DOI: 10.1021/acssuschemeng.0c05465
|View full text |Cite
|
Sign up to set email alerts
|

Laminated Cellulose Hybrid Membranes with Triple Thermal Insulation Functions for Personal Thermal Management Application

Abstract: Wearable textiles with multiple thermal insulation functions would play a significant role in preventing heat loss and improving personal thermoregulation properties. However, the precise control over the wearable materials with integrated insulation properties as well as the mechanical properties and antibacterial properties remains a challenge. Herein, the laminated cellulose hybrid membrane (LCHM) with triple thermal insulation functions was prepared by orderly vacuum filtration of cattail stick cellulose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Integrating personal thermoregulation technologies into wearable textiles has enabled extensive and profound technological breakthroughs in energy savings, thermal comfort, wearable electronics, intelligent fabrics ( Peng and Cui, 2020 ; Tabor et al., 2020 ). Nevertheless, previous studies have suffered from long-standing issues such as limited working temperature, poor comfort, and weak textile reliability ( Gu et al., 2020 ; Li et al., 2021b ). Encapsulating PCMs into fibers is a facile and effective approach to solve the leakage problem and improve the thermal performances of flexible textiles ( Tang et al., 2018 ).…”
Section: Advanced Flexible Composite Pcmsmentioning
confidence: 99%
“…Integrating personal thermoregulation technologies into wearable textiles has enabled extensive and profound technological breakthroughs in energy savings, thermal comfort, wearable electronics, intelligent fabrics ( Peng and Cui, 2020 ; Tabor et al., 2020 ). Nevertheless, previous studies have suffered from long-standing issues such as limited working temperature, poor comfort, and weak textile reliability ( Gu et al., 2020 ; Li et al., 2021b ). Encapsulating PCMs into fibers is a facile and effective approach to solve the leakage problem and improve the thermal performances of flexible textiles ( Tang et al., 2018 ).…”
Section: Advanced Flexible Composite Pcmsmentioning
confidence: 99%
“…43 One of the proposed strategies to develop thermal management structures is using thermally conductive fillers such as boron nitride (BN). 212,213 Using a well interpenetrated BN network within a nanofibrous membrane, highly thermal conductive breathable NFMs can be developed. 7 In-plane and out-plane thermal conductivity was 17.9 and 0.29 W m À1 K À1 , in the composite membrane obtained in this method.…”
Section: Thermal Conductive Membranesmentioning
confidence: 99%
“…For example, maintaining a body core temperature is important for life activities; 12% of the total energy consumption in the United States is for maintaining indoor space temperature . Currently, power-consuming equipment, such as air conditioning, electric blankets, and floor heating facilities, are used to maintain indoor space temperature resulting in a considerable amount of energy consumption. , In this context, a personal precise thermal management strategy is proposed, which can not only reduce the energy consumption of inanimate objects but also has no space limitations compared with space thermal management methods because it mainly focuses on the microenvironment of human skin. , In this respect, Gu et al reported laminated cellulose aerogel membranes with triple thermal insulation properties for personal thermal management application. However, the unidirectional liquid penetration properties of laminated membranes are limited by amphiphilic interfaces .…”
Section: Introductionmentioning
confidence: 99%